Antihypertensive effects of yoga in a general patient population: real-world evidence from electronic health records, a retrospective case-control study - Nadia M. Penrod; Jason H. Moore (BMC, 2022)
Abstract Background Despite decades of research and established treatment strategies, hypertension remains a prevalent and intractable problem at the population level. Yoga, a lifestyle-based practice, has demonstrated antihypertensive effects in clinical trial settings, but little is known about its effectiveness in the real world. Here, we use electronic health records to investigate the antihypertensive effects of yoga as used by patients in their daily lives. Methods A retrospective, observational case-control study of 1815 records among 1355 yoga exposed patients and 40,326 records among 8682 yoga non-exposed patients collected between 2006 and 2016 from a regional academic health system. Linear mixed-effects models were used to estimate the average treatment effect of yoga on systolic and diastolic blood pressures. Mixed effects logistic regression models were used to calculate odds ratios for yoga use and four blood pressure categories: normal, elevated, stage I, and stage II hypertension. Results Yoga patients are predominantly white (88.0%) and female (87.8%) with median age 46 years (IQR 32-57) who use yoga one time per week (62.3%). Yoga is associated with lower systolic (− 2.8 mmHg, standard error 0.6; p < .001) and diastolic (− 1.5 mmHg, standard error 0.5; p = 0.001) blood pressures. Patients using yoga have 85% increased odds (OR 1.85, 95% CI 1.39-2.46) of having normal blood pressure relative to yoga non-exposed patients. Patients aged 40-59 years have 67% decreased odds (0.33, 95% CI 0.14-0.75) of having stage II hypertension. All effect sizes are age-dependent. Conclusions Yoga, as used by patients in their daily lives, may be an effective strategy for blood pressure control and the prevention of hypertension at the population level.